2012
DOI: 10.1186/1741-7015-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions for overweight and obese pregnant women to improve pregnancy outcome: systematic review and meta-analysis

Abstract: BackgroundOverweight and obesity pose a big challenge to pregnancy as they are associated with adverse maternal and perinatal outcome. Evidence of lifestyle intervention resulting in improved pregnancy outcome is conflicting. Hence the objective of this study is to determine the efficacy of antenatal dietary, activity, behaviour or lifestyle interventions in overweight and obese pregnant women to improve maternal and perinatal outcomes.MethodsA systematic review and meta-analyses of randomised and non-randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
250
5
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(274 citation statements)
references
References 55 publications
(74 reference statements)
15
250
5
4
Order By: Relevance
“…Of the 74 eligible studies (17,727 women), 36 (12,434 women) contributed data to the IPD meta-analysis: 33 (9320 women) evaluated GWG, 24 (8852 women) reported all four components of the composite maternal outcomes and 18 (7981 women) assessed all four components of the fetal/neonatal composite outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 74 eligible studies (17,727 women), 36 (12,434 women) contributed data to the IPD meta-analysis: 33 (9320 women) evaluated GWG, 24 (8852 women) reported all four components of the composite maternal outcomes and 18 (7981 women) assessed all four components of the fetal/neonatal composite outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Subgroup effects are rarely reported in sufficient detail, especially to derive differences in intervention effect between subgroups ('treatment-covariate interactions'). Meta-regression examining the across-trial association between overall treatment effect and average patient characteristics (e.g.…”
Section: Differential Effect Of Interventions On Gestational Weight Gmentioning
confidence: 99%
“…The results of several intervention trials aimed at reducing GDM have been inconsistent and discouraging [7]. We hypothesised that these inconsistent results may in part be due to genetic factors, such as the rs10830963 polymorphism in MTNR1B.…”
Section: Introductionmentioning
confidence: 99%
“…To date, existing interventions to prevent excessive weight gain are so limited in number and effectiveness, that both the IOM [32] and the Agency for Health care Research and Quality (AHRQ) [33] have identified this as a major research gap. Interventions based on physical activity and dietary counseling, usually combined with supplementary weight monitoring [34,35], have had modest success in reducing the amount of excessive weight gained during pregnancy, but few efforts have been effective enough for women to gain within their IOM target range [36,37]. Thus, we need to design effective interventions that prevent excessive weight gain during pregnancy that are widely effective, practical, cost-effective, and have mechanisms for widespread diffusion.…”
Section: Shifting Perspectivesmentioning
confidence: 99%